1995
DOI: 10.1161/01.cir.92.12.3436
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Relation Between Myocardial Viability and Improvement in Heart Failure Symptoms After Revascularization in Patients With Ischemic Cardiomyopathy

Abstract: In patients with ischemic cardiomyopathy, the magnitude of improvement in heart failure symptoms after CABG is related to the preoperative extent and magnitude of myocardial viability as assessed by use of PET imaging. Patients with large perfusion-metabolism mismatches exhibit the greatest clinical benefit after CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
0
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(145 citation statements)
references
References 27 publications
4
137
0
4
Order By: Relevance
“…Discerning the etiology of LV dysfunction is often the first step in management. Underlying coronary artery disease (CAD) and ischemia are responsible for approximately two-thirds of all systolic dysfunction [1] and delineating it from nonischemic causes has essential therapeutic [2,3,4] and prognostic [5,6,7,8] implications. The electrocardiogram (ECG) [9], presence of anginal chest pain [10], and elevated troponins [11] are unable to accurately differentiate ischemic from nonischemic cardiomyopathy (NICM).…”
Section: Introductionmentioning
confidence: 99%
“…Discerning the etiology of LV dysfunction is often the first step in management. Underlying coronary artery disease (CAD) and ischemia are responsible for approximately two-thirds of all systolic dysfunction [1] and delineating it from nonischemic causes has essential therapeutic [2,3,4] and prognostic [5,6,7,8] implications. The electrocardiogram (ECG) [9], presence of anginal chest pain [10], and elevated troponins [11] are unable to accurately differentiate ischemic from nonischemic cardiomyopathy (NICM).…”
Section: Introductionmentioning
confidence: 99%
“…More than three decades ago, Neely and colleagues (35,37) showed that ischemia reduces glucose uptake and glycolysis. However, those results contrast with positron emission tomography studies that show an increase in the uptake of 18 F-deoxyglucose in relation to coronary flow in patients with coronary artery disease (10,32). Similar observations in vivo (50) and ex vivo (40,45) were attributed to a translocation of GLUT4 to the cell surface, due to ischemiainduced activation of adenosine 5Ј-monophosphate-activated protein kinase (AMPK) (39).…”
mentioning
confidence: 76%
“…The presence of myocardial viability appears to help to predict those patients most likely to manifest improved symptoms and reversibility of chronic LV dysfunction (33)(34)(35)(36)(37)(38)(39)(40). The assessment of myocardial viability is therefore important to identify patients with a significant amount of viable, dysfunctional myocardium that is likely to recover function if revascularized with adequate blood flow.…”
Section: The Role Of Evaluation Of Myocardial Viabilitymentioning
confidence: 99%
“…The assessment of myocardial viability is therefore important to identify patients with a significant amount of viable, dysfunctional myocardium that is likely to recover function if revascularized with adequate blood flow. A variety of imaging techniques have helped to characterize the presence of viable but dysfunctional myocardial tissue, for example, myocardial perfusion imaging with radionuclide flow tracers, positron emission tomography (PET) imaging with 18 F-fluorodeoxyglucose, and assessment of inotropic reserve through echocardiographic or nuclear imaging under catecholamine stimulation (33)(34)(35)(36)(37)(38)(39)(40).…”
Section: The Role Of Evaluation Of Myocardial Viabilitymentioning
confidence: 99%